Analisis Kinerja Laporan Keuangan Daerah Kabupaten Sidoarjo - Azizahtut Ta’zhiyah; Lilis Ardini (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This research aims to assess the performance of the Sidoarjo Regency government in terms of the Regional Financial Report for the period 2022 and 2021. The object and research data used is the Sidoarjo Regency Government Financial Report for the period 2022 with a comparison of 2021. This research is a qualitative descriptive research with analysis of the Regional Financial Report. This comparative analysis was carried out because in the previous year, namely 2021, fraud behavior regarding government funds was discovered. The results of the existing analysis show that the performance of the Sidoarjo Regency government in 2022 has experienced significant improvements compared to 2021.